Cough – the diagnosis and treatment in palliative care patients - Zasowska-Nowak, Anna; Ciałkowska-Rysz, Aleksandra (Medycyna Paliatywna/Palliative Medicine, 2018)
Prevalence of chronic cough in palliative care patients is estimated at about 10-70% among cancer patients and 60-95% among patients with pulmonary and cardiovascular end-stage diseases. In cancer patients cough can be a symptom of an underlying main pathology, concomitant disorders or side effects of treatment. Sustained, burdensome cough has a negative impact on quality of life, escalating fatigue and signs of general distress, leading to sleep disorders, poor control of symptoms (pain, breathlessness) and worsening of social relations. Identification of the underlying cause facilitates making a decision regarding proper therapy: causative treatment (when appropriate), withdrawal of drugs that potentiate the cough reflex, optimization of concomitant disorders’ treatment or application of non-pharmacological procedures. In the case of ineffectiveness of mentioned measures, administration of drugs of proven efficacy against cough (levodropropizine, butamirate, morphine, codeine, dihydrocodeine, dextromethorphan, sodium cromoglycate) is necessary.